2020
DOI: 10.3389/fpls.2020.00391
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Landscape of Medicinal Dendrobium Reveals Genes Associated With the Biosynthesis of Bioactive Components

Abstract: Many plants of Dendrobium genus are precious traditional herbs with high commercial value and excellent medicinal effects. They are perennial aerophytes or epiphytes of terrestrial orchids growing on cliffs and tree trunks covered with mosses in forests throughout the tropical and subtropical Asia and eastern Australia. The stem contains a variety of bioactive components, including polysaccharides and alkaloids, with strong antioxidant, neuroprotective, and immunomodulatory effects. Great attention has been dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 138 publications
(94 reference statements)
1
37
0
Order By: Relevance
“…Dendrobine (20) belongs to the class of terpenoid indole alkaloids (TIAs) ( Wang et al, 2020 ). The biogenetic pathway of TIAs is conservative among alkaloid-producing plants ( Li Q. et al, 2017 ).…”
Section: Chemical Synthesis and Biosynthetic Pathway Of Dendrobinementioning
confidence: 99%
“…Dendrobine (20) belongs to the class of terpenoid indole alkaloids (TIAs) ( Wang et al, 2020 ). The biogenetic pathway of TIAs is conservative among alkaloid-producing plants ( Li Q. et al, 2017 ).…”
Section: Chemical Synthesis and Biosynthetic Pathway Of Dendrobinementioning
confidence: 99%
“…In plant breeding and horticulture, transcriptome sequencing is highly employed for predicting novel genes, gene function, and genome evolution [ 11 ]. Here, we performed whole-transcriptome sequencing to study the mechanism of purple color development in D. nestor petals, which is the first report, as compared to other Dendrobium species [ 13 , 69 , 70 , 71 , 72 ]. H and B samples might have relatively similar anthocyanins accumulation and synthesis, hence the high similarity as evident in Figure 1 a,b and Figure 4 b.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical isolation of compounds has identified diverse active compounds including polysaccharides, flavonoids, alkaloids, and multiple amino acids. In particular, the polysaccharides, alkaloids, and flavonoids extracted from D. officinale are thought to be the main bioactive ingredients for medicine ( Meng et al, 2016 ; Tang et al, 2017 ; Wang et al, 2020 ; Wang, 2021 ). Pharmacological studies have confirmed the positive effects of polysaccharides, alkaloids and flavonoids extracted from D. officinale on immune regulation and liver protection ( Wang et al, 2020 ), on anti-cancer and neuroprotection ( Zhang et al, 2003 ; Wang et al, 2020 ), and on anti-oxidant activity ( Yuan et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%